Kiais, Authoritarianism, and Sinful Tourism in Madura - Quraisyin, Dewi; Hanif, Naufal Aulia (ESENSIA: Jurnal Ilmu-Ilmu Ushuluddin, 2022)
The economy can play a role in the resurgence of tourism on Madura Island, which has been known as a hidden paradise. Madura has a great tourism potential that needs to be maximally improved in order to overcome its economic problems. However, given its socio-cultural context, Madura is not sufficiently receptive to tourism. Several factors, including the rejection of the kiais (religious leaders/teachers), have contributed to the underdevelopment of Madura’s tourism industry. In Madura, a kiai serves as a religious and social figure with considerable influence in Madurese society who adhere to the philosophy of Buppa', Babbu, Guru, Rato (“Father-Mother, Teacher, Government”). This qualitative research found a conflict of interests between two groups: the kiais as the guardian of culture and religion and the managers as a modern progressive group. In addition, I conclude that the efforts made by the kiais as social elites in rejecting the development of tourism in Lon Malang Beach show that there is a power of authority that makes it easier for the kiais to maintain their conservative religious views and reject any upcoming changes.